Auditory-Dependent Vocal Recovery in Adult Male Zebra Finches Is Facilitated by Lesion of a Forebrain Pathway That Includes the Basal Ganglia - Thompson, John A. (J Neurosci, 2007)
The integration of two neural pathways generates learned song in zebra finches. The vocal motor pathway (VMP) is a direct connection between HVC (proper name) and the robust nucleus of the arcopallium (RA), whereas the anterior forebrain pathway (AFP) comprises an indirect circuit from HVC to RA that traverses the basal ganglia. Partial ablation (microlesion) of HVC in adult birds alters the integration of VMP and AFP synaptic input within RA and destabilizes singing. However, the vocal pattern shows surprising resilience because birds subsequently recover their song in ∼1 week. Here, we show that deafening prevents vocal recovery after HVC microlesions, indicating that birds require auditory feedback to restore/relearn their vocal patterns. We then tested the role of the AFP (basal ganglia circuit) in this feedback-based recovery by ablating the output nucleus of the AFP [lateral magnocellular nucleus of the anterior nidopallium (LMAN)]. We found that LMAN ablation after HVC microlesions induced a sudden recovery of the vocal pattern. Thus, the AFP cannot be the neural locus of an instructive/learning mechanism that uses auditory feedback to guide vocal recovery, at least in this form of adult vocal plasticity. Instead, the AFP appears to be the source of the variable motor patterns responsible for vocal destabilization. In part, auditory feedback may restore song by strengthening the VMP component of synaptic input to RA relative to the AFP component.